2008
DOI: 10.1007/s11284-008-0545-6
|View full text |Cite
|
Sign up to set email alerts
|

Tidal effects on the organic carbon mineralization rate under aerobic conditions in sediments of an intertidal estuary

Abstract: Laboratory experiments and field measurements were conducted to examine the effect of tide on the organic carbon mineralization rate in sediments under aerobic conditions of an intertidal estuary. Core samples of surface sediments were collected from an intertidal estuary of the Kurose River, Hiroshima, Japan. To mimic low and high tide in the intertidal estuary, organic carbon mineralization rates in the samples were measured in the laboratory under both air-exposed and submerged conditions. Mineralization ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…The effect of the tide on the sediment respiration rates was also considered in the model because a previous study reported that the tide affected the respiration rates, and the rate under air-exposed conditions was higher than the rate under submerged conditions (Sasaki et al 2009). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the tide on the sediment respiration rates was also considered in the model because a previous study reported that the tide affected the respiration rates, and the rate under air-exposed conditions was higher than the rate under submerged conditions (Sasaki et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…where R E(T) is the sediment respiration rate (mg CO 2 -C m -2 h -1 ) under air-exposed conditions at sediment temperature T (°C); R S(T 0 ) is the sediment respiration rate (mg CO 2 -C m -2 h -1 ) under submerged conditions at sediment temperature T 0 (°C); R E(30) is 38.8 mg CO 2 -C m -2 h -1 (mean of in situ sediment respiration rates at a sediment temperature 30°C); R S(30) is 16.9 mg CO 2 -C m -2 h -1 (based on a value for R E(T) /R S(T) of 2.3; Sasaki et al 2009); t is the duration of submerged conditions per day (h); and Q 10 is 1.8 (this study; Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the temporal variations in CO 2 and CH 4 effluxes were positively correlated with change in the water table in the littoral zone of Lake Obuchi, Japan (Yamamoto et al 2009(Yamamoto et al , 2011. Also, CO 2 emission was reported to be greatly inhibited by submersion in the Kurose River estuary of Japan (Sasaki et al 2009). These studies were conducted across the semi-diurnal cycle, mainly in STP when soils were inundated or water-saturated most of the time.…”
Section: Introductionmentioning
confidence: 98%
“…The marine water supply usually conveys dissolved oxygen (DO) to the system. Moreover, exposure to the air of intertidal sediments at low tide significantly increases mineralization rates (Sasaki et al, 2009). Remineralization processes can be enhanced by water mixing because of both oxygenation and increased contact of catabolites with various kinds of surface, such as bottom sediments, suspended matter and other physical and biological components (e.g.…”
Section: The Concept Of Saprobitymentioning
confidence: 99%